META ANALISIS: FAKTOR PEMICU TERJADINYA DERMATITIS ATOPIK PADA ANAK - Eka Sari, Luthfiana; Haq, Arini; Rakhmawati, Yustian (Jurnal Klinik dan Riset Kesehatan, 2023)
Background: Atopic dermatitis is a non-communicable skin disorder characterized by intense itching. It is relapsing, recurring, and can have a negative impact on the quality of life of patients and their family members. Atopic dermatitis occurs most often in early infancy and childhood. Atopic dermatitis can occur if there is dysregulation of IgE resulting in a breakdown of the epidermal barrier. There are several factors that trigger the occurrence of atopic rheumatism in children, which can come from environmental factors or medical history. Aim: For this reason, this study aims to analyze the similarity of output regarding the magnitude of risk factors for atopic dermatitis in children. Methods: This study was analyzed using a meta-analysis using PRISMA, where there were 7 of 8654 articles that met the criteria for analysis. Meanwhile, the data presentation was carried out using a forest plot with a random effect statistical model. Results: The presence of pets, children living in environments that have pets (cats or dogs) are known to increase the risk of atopic dermatitis by 5 times compared to children living in environments that do not have animals. pet. The health history factor seen from exclusive breastfeeding, where babies who are exclusively breastfed are significantly less likely to experience atopic dermatitis by 12.5 times compared to babies who are not exclusively breastfed. Conclusion: Not giving exclusive breastfeeding and pets affect atopic dermatitis in children (p<0,05).